Reorganizacija centrov za socialno delo kot izziv za uporabo sodobnih konceptov socialnega dela - Žnidar, Aleš (Socialno delo, 2020)
The reorganization of centres for social work that was implemented in 2018 by the Ministry of Labour, Family, Social Affairs and Equal Opportunities has been the subject of much criticism since its planning. It was supposed to provide opportunities for contemporary professional social work, but, according to the results of a qualitative survey based on partially structured interviews and on a non-probability convenience sample of eight directors and eight social workers of centres for social work, even half a year after the start of the reorganization its aim is still not fulfilled. The participants of the survey see some advantages, for example in the (not yet implemented) transfer of the exercise of rights from public funds to a special unit, in more cooperation between professionals and employees of different centres for social work units, and in the harmonization of employment contracts. There are, however, many more identified challenges: on the ministry level, in management of centres for social work, in staffing, and in professional social work. They indicate that the current state of affairs is more of a hindrance than an incentive to use modern social work concepts. Some amendments for improvements are listed and described that would be more in accordance with modern concepts of social work.
Keywords: human resources; kadri; kvalitativna raziskava; ministrstvo; ministry; participacija; participation; profession; qualitative research; social security; socialno varstvo; stroka